Sequential filtration and interpolation of components of Markov chains - Glonti, O. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:О. А. Глонти. Последовательная фильтрация и интерполяция компонент марковской цепиO. Glontis. Markovo grandinės komponenčių nuosekli filtracija ir interpoliacija